How can augmented reality add value for companies: benefits and challenges of its application in marketing - Kemm, Felicitas Marie (2017)
The present study aims to gain a better understanding of the reasons influencing the use of AR applied in marketing. Besides its promising success in the literature, there is still a risk that Augmented Reality does not add value to the company. Marketers must decide whether and how the technology can be applied in favor of the company. A case study research with three companies using or used Augmented Reality in their business was applied. The data were collected via semi-structured interviews with marketing experts’ from each company. Based on the findings of the interviews, the reasons why companies applied Augmented Reality are: the belief that there is a need for it, a better communication with their customers, the need to appear innovative, and a decrease in the return- and increase in the conversion rate. In fact, this research revealed that after the implementation of Augmented Reality two out of three companies had a better market performance in terms of an increase in the demand, or a better conversion rate, more time spent on the product page with the Augmented Reality tool, and a decrease in their return rate. However, one case also demonstrated that even though an increasing market performance, Augmented Reality can still fail due to reasons such as technical issues.